A Successful Treatment Of Dystocia Due To Incomplete Dilatation Of Cervix In Cow By Misoprostol - Shah, M.A.; Shah, I.A.; Hussain, Khalid; Kumar, Suneel; Negi, S.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Incomplete dilatation of the cervix is a common cause of dystocia in cattle (Noakes et al., 2002). Cervical priming refers to dilatation and softening of the cervix in the first stage of labor and is a gradual process (Jackson, 2004). Incomplete dilatation in multiparous cows may be associated with uterine inertia caused by hypocalcaemia; in these animals, the response to calcium therapy is rapid. Misoprostol an analogue of prostaglandin E1 is widely used to ripen the cervix and/or initiate labor at term in human and it is more widely used to control postpartum bleeding (Fiala et al., 2007; Weeks et al., 2007). PGE1 has never been used in bovine obstetrics to dilate the incompletely dilated cervix causing dystocia. This report describes probably the first successful use of misoprostol (PGE1) for the treatment of incomplete dilatation of cervix in a local non-descript cow.